FORMULATION AND EVALUATION OF COSMETIC FOUNDATION USING EPIGALLOCATECHIN GALLATE AS A SUN PROTECTION - ANWAR, EFFIONORA; RIZKAMIARTY, SHIFA (International Journal of Applied Pharmaceutics, 2020)
Objective: The objective of the study was to obtain a lotion foundation using epigallocatechin gallate (EGCG) as an active ingredient designed with a sun protection factor (SPF) value around 30 that can effectively protect facial skin from ultraviolet radiation (UVR) exposure and that is safe to use. Methods: In this study, we determine SPF value using UV–visible spectrophotometry at a wavelength between 290 and 320 nm. The preparation formula of the foundation was made with an EGCG concentration of 0.4%, a concentration which can yield the desired SPF value of about 30. Physical stability was performed at low (4±2°C), ambient (25±2°C), and high (40±2°C) temperatures; cycling and centrifugation tests were also conducted. Safety was evaluated by eye irritation test using hen’s egg test on chorioallantois method and skin irritation test using the Draize and patch tests method. Results: The SPF values of 0.04% EGCG and lotion foundation containing 0.4% EGCG were 31.02±0.72 and 33.20±0.59, respectively. The results of cycling and centrifugal tests indicated that lotion foundation showed an absence of crystals and lack of any phase separation between oil and water phases. The physical stability test showed no significant changes for all parameters. Safety tests resulted in neither skin nor eye irritation. Conclusion: The EGCG foundation developed was physically stable with a good appearance and did not irritate the skin or eyes thus are safe to use also can effectively protect skin against UVR exposure.